Модель расследования преступлений и средства криминалистической тактики - Шепитько, Валерій Юрійович; Шепитько, Валерий Юрьевич; Shepit'ko, Valerij (My University, 2012)
The article is devoted to the procedure for the criminal offence investigation and some changes in the criminal procedure in became of the adoption a new Criminal Procedure Code of Ukraine. The intercommunication between procedure orders and criminalistic recommendations her been determined. Special attention is payied to certain criminalistic tactical tendencies in modern conditions.
Шепитько В. Ю. Модель расследования преступлений и средства криминалистической тактики / В. Ю. Шепитько // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 447-455.
Keywords: расследование преступлений; криминалистическая тактика; досудебное расследование; состязательные начала; следователь; установление истины; тактические приемы; криминалистические рекомендации; розслідування злочинів; криміналістична тактика; досудове розслідування; змагальні засади; слідчий; встановлення істини; слідчі дії; тактичні прийоми; криміналістичні рекомендації; investigation of crimes; criminalistic tactics; preliminary investigation; controversial basis; investigator; ascertainment of the truth; investigating actions; tactical methods; criminalistic recommendations